Minimum 10 Year Clinical and Radiological Outcomes of a Randomized Controlled Trial Evaluating Accelerated Weight Bearing After Matrix-Induced Autologous Chondrocyte Implantation. Issue 7 (29th July 2019) - Ebert, Jay R.; Fallon, Michael; Janes, Greg; Wood, David
Objectives: Matrix-induced autologous chondrocyte implantation (MACI) has demonstrated encouraging clinical outcomes in the treatment of symptomatic knee chondral defects. However, longer term results are still lacking and post-operative management has traditionally been conservative, with little available evidence on how best to progressively increase weight bearing (WB) and rehabilitation post-surgery. This study sought to investigate the longer term clinical and radiological outcomes following an accelerated (versus conservative) WB protocol after MACI. Methods: A randomized controlled study design was used to investigate outcomes in 70 patients who underwent MACI to the medial or lateral femoral condyle between November 2005 and November 2007, in conjunction with either an accelerated (AR, n=34, 8 weeks to full WB) or conservative (CR, n=36, 12 weeks to full WB) approach to post-operative WB rehabilitation. Patients were evaluated pre-surgery and at 3, 6, 12 and 24 months, as well as 5 years post-surgery. At minimum 10 year follow up (range 10.5-11.5 years), 60 patients (86%, AR=31, CR=29) were available for review. Clinical outcomes included the IKDC, KOOS, Lysholm, Cincinnati, Tegner, SF-36, Satisfaction, maximal isokinetic knee extensor and flexor strength and functional hop capacity. Limb Symmetry Indicies (LSIs) comparing the operated and non-operated limbs were calculated for strength and functional measures. High resolution magnetic resonance imaging (MRI) was undertaken to assess the quality and quantity of repair tissue as per the magnetic resonance observation of cartilage repair tissue (MOCART) scoring system. A combined MRI composite score was also evalauted. ANOVA investigated group differecnes over time. Results: While the AR group reported significantly less knee pain in the earlier post-operative timeline, no significant differences (p>0.05) were observed in patient demographics or injury/surgery characteristics between groups, nor clinical and MRI-based scores, at minimum 10 year post-operative follow up. All clinical scores across both groups significantly improved (p<0.001) to 5 years, maintained to 10 years. At minimum 10 years, no differences were observed in mean LSIs for maximal isokinetic knee extension strength (AR=96.8%, CR=97.9%), or the single (AR=95.5%, CR=98.9%) and triple hop (AR=96.7%, CR=99.6%) tests for distance. At a minimum 10 years 82.4% and 83.3% of patients in the AR and CR groups, respectively, demonstrated a good-excellent MRI composite score, while 79.4% and 83.3% demonstrated good-excellent tissue infill, as per the MOCART score. Graft failure was observed on MRI in 5 patients (8.3%, AR=2, CR=3) at 10 years post-surgery. At 10 years, 93.3% of patients were satisfied with MACI for relieving their pain, with 83.4% satisfied with their ability to participate in sport. Conclusion: MACI provided high levels of patient satisfaction and tissue durability beyond 10 years. The outcomes of this randomized trial demonstrate a safe and effective accelerated WB rehabilitation protocol, with improved early patient outcomes albeit comparable longer term results.